Drought Tolerant Capability of Pineapple (Ananas comosus (L.) Merr) Plant Microbiome - Rahayu Fitriani Wangsa Putrie; I Nyoman Pugeg Aryantha; Iriawati; Sarjiya Antonius (Tropical Life Sciences Research, 2025)
The microbiomes of Indonesian pineapple plants cover drought-resistant microorganisms that have not yet been studied. Therefore, this research aims to analyse the pineapple’s endophytic and rhizobacteria capability to survive and support the plant in drought. The screening used polyethylene glycol (PEG) 6000 with specific osmotic pressures as a form of stress simulation. The isolates were further tested for their production of exopolysaccharides (EPS) and growth hormones (IAA), survival at high temperatures and salinity and other vital, drought-tolerant factors. Based on PEG 6000 analysis with certain osmotic pressure, about 13 isolates could survive at –0.73 MPa. Some isolates can produce EPS up to 89.23 mg/mL at –0.73 MPa, survive at 10% salinity, at a temperature of 50°C, pH 4 and produce IAA up to 7.5 ppm on medium. Most isolates can improve corn seedlings’ growth quality and produce ACC deaminase and catalase enzymes. Isolate BDO 8 and BAO 5 showed more constant results compared with others. Based on the 16S rRNA gene, these isolates were identified as Bacillus cereus strain ATCC 14579T.112 and Bacillus cereus strain WHX1 with 99.91% and 100% sequence similarities, respectively. These findings suggest that these isolates could be developed as bioinoculant candidates for use in dry agricultural areas.